Heat Shock Treatment Promoted Callus Formation on Postharvest Sweet Potato by Adjusting Active Oxygen and Phenylpropanoid Metabolism - Qi Xin; Bangdi Liu; Jing Sun; Xinguang Fan; Xiangxin Li; Lihua Jiang; Guangfei Hao; Haisheng Pei; Xinqun Zhou (Agriculture, 2022)
This study aimed to investigate that rapid high-temperature treatment (RHT) at an appropriate temperature could accelerate callus formation by effectively promoting the necessary metabolic pathways in sweet potato callus. In this study, the callus of sweet potato was treated with heat shock at 50, 65, and 80 °C for 15 min. The callus formation was observed within 1, 3, and 5 days, and the accumulation of intermediates in the metabolism of phenylpropane and reactive oxygen species and changes in enzyme activities were determined. The results showed that appropriate RHT treatment at 65 °C stimulated the metabolism of reactive oxygen species at the injury site of sweet potato on the first day, and maintained a high level of reactive oxygen species production and scavenging within 5 days. The higher level of reactive oxygen species stimulated the phenylalanine ammonia-lyase (PAL), 4-coumarate-CoA ligase and cinnamate-4-hydroxylase activities of the phenylpropane metabolic pathway, and promoted the rapid synthesis of chlorogenic acid, p-coumaric acid, rutin, and caffeic acid at the injury site, which stacked to form callus. By Pearson’s correlation analysis, catalase (CAT), PAL, and chlorogenic acid content were found to be strongly positively correlated with changes in all metabolites and enzymatic activities. Our results indicated that appropriate high-temperature rapid treatment could promote sweet potato callus by inducing reactive oxygen species and phenylpropane metabolism; moreover, CAT, PAL, and chlorogenic acid were key factors in promoting two metabolic pathways in sweet potato callus.